2005
DOI: 10.1074/jbc.m500926200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Receptors EP2 and EP4 Are Down-regulated during Differentiation of Mouse Osteoclasts from Their Precursors

Abstract: Prostaglandin E 2 (PGE 2 ) has been proposed to be a potent stimulator of bone resorption. However, PGE 2 itself has been shown to directly inhibit bone-resorbing activity of osteoclasts. We examined the role of PGE 2 in the function of mouse osteoclasts formed in vitro. Bone marrow macrophage osteoclast precursors expressed PGE 2 receptors EP1, EP2, EP3␤, and EP4, and the expression of EP2 and EP4 was down-regulated during osteoclastic differentiation induced by receptor activator of NF-B ligand and macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Additionally, the stimulation of gastric cancer cells with PTGER2 agonists results in significant growth inhibition (35). A similar escape mechanism was described in non-malignant myeloid precursors of osteoclasts that try to escape PGE2-induced inhibition of bone resorption by down-regulation of their PTGER2 receptor (36).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, the stimulation of gastric cancer cells with PTGER2 agonists results in significant growth inhibition (35). A similar escape mechanism was described in non-malignant myeloid precursors of osteoclasts that try to escape PGE2-induced inhibition of bone resorption by down-regulation of their PTGER2 receptor (36).…”
Section: Discussionmentioning
confidence: 88%
“…Hence, Kobayashi et al (36,37) demonstrated that PTGER2 is up-regulated in immature myeloid precursors and thus becomes down-regu- lated after the cells have differentiated into osteoclasts. Thus, further studies will show whether down-regulation of PTGER2 either provokes an escape mechanism from PGE2-derived immunomodulatory effects in the bone marrow niche or modulates differentiation of immature preleukemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In general, bone formation and bone resorption occur simultaneously in equilibrium, and they are regulated by systemic hormones (such as vitamin D and parathyroid hormone) [48,49], bone-derived local factors including prostaglandins [48], proinflammatory cytokines [48][49][50], nitric oxide [51] and the function of immune cells [52]. Among the prostaglandin E 2 (PGE 2 ) produced by osteoblastic lineage [53] is a potent local factor stimulating bone resorption both in vivo [54] and in vitro [54,55] in response to the catabolic effects of vitamin D, parathyroid hormone and cytokines [56,57]. In vitro studies [58][59][60] show that effects of PGE 2 on bone formation are biphasic and concentration dependent.…”
Section: Discussionmentioning
confidence: 99%
“…EP1 causes elevations in intracellular Ca 2+ by coupling with Gq 13 . Osteoclasts express all PGE 2 receptors, and production of intracellular Ca 2+ through EP1 or production of cAMP and activation of protein kinase A (PKA) through EP2 or EP4 are critical for osteoclast cell differentiation 11,12,14,15 .…”
Section: Introductionmentioning
confidence: 99%